Skuteczne zarządzanie projektami w przedsiębiorstwie - Kacała, Joanna; Wąsowicz, Marek (The Effective Project Management in the Company, 2006)
In this article some factors which influence the effective management projects in the company теге described. They are as follows: appointing the project manager, describing the goal of the pro-eel in the clear way, appointing the project team, supporting the management board of the company or the project. The main reasons of the failure of the projects were also mentioned. The authors described some ways of rising the effectiveness of the project management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 311-317